SANITASI LINGKUNGAN DAN PERILAKU KELUARGA TERHADAP KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) - Cania, Arriy Saputra; Dewi, Oktavia; Alamsyah, Agus (Ensiklopedia of Journal, 2022)
Dengue Hemorrhagic Fever (DHF) is an acute febrile disease accompanied by hemorrhagic manifestations with a tendency to cause shock and can cause death, generally attacks children < 15 years, but it is possible to attack adults. In Rokan Hulu there was an increase in dengue cases for three years. the last year starting from 2017-2019. In 2017 there were 61 cases with an incidence rate of 15.95 per 100,000 population, in 2018 there were 77 cases with an incidence rate of 20.13 per 100,000 population, and in 2019 there were 79 cases with an incidence rate of 20.65 per 100,000 population.Objective: to determine the relationship between environmental sanitation and family behavior on the incidence of Dengue Hemorrhagic Fever (DHF) in Ujung Batu District, Rokan Hulu Regency.Methods: This type of research is quantitative and case control design. The population in this study were all households in the Ujung Batu Health Center, with a sample of 105 people, the sampling technique used was simple random sampling. Using primary data, with instruments using observation sheets and questionnaires. Data analysis used univariate, bivariate and multivariate analysis.Results: The type of water reservoir that does not meet the requirements has a risk of 7.183 times the incidence of DHF, the habit of sleeping in the morning and evening has a risk of 2.811 times to experience the incidence of DHF, and the cofounding variable is ventilation.Conclusion: The type of water reservoir that does not meet the requirements and the habit of sleeping in the morning and afternoon have a significant effect on the incidence of dengue fever (DHF).